Strain Breeding Enhanced Heterologous Cellobiohydrolase Secretion by Saccharomyces cerevisiae in a Protein Specific Manner. Issue 10 (15th September 2017) - Kroukamp, Heinrich; den Haan, Riaan; la Grange, Daniël C.; Sibanda, Ntsako; Foulquié‐Moreno, Maria R.; Thevelein, Johan M.; van Zyl, Willem H.
Abstract : The yeast Saccharomyces cerevisiae has a long association with alcoholic fermentation industries and has received renewed interest as a biocatalyst for second‐generation bioethanol production. Rational engineering strategies are used to create yeast strains for consolidated bioprocessing of lignocellulosic biomass. Although significant progress is made in this regard with the expression of different cellulolytic activities in yeast, cellobiohydrolase (CBH) titers remain well below ideal levels. Through classical breeding, S. cerevisiae strains with up to twofold increased CBH secretion titers is obtained in strains expressing a single gene copy. An increase of up to 3.5‐fold in secreted cellobiohydrolase activity is subsequently shown for strains expressing the heterologous gene on a high copy episomal vector. To our knowledge, this is the first report of classical breeding being used to enhance heterologous protein secretion and also the most significant enhancement of CBH secretion in yeast yet reported. This enhanced secretion phenotype is specific for cellobiohydrolase I secretion, indicating that reporter protein properties might be a major determining factor for efficient protein secretion in yeast. By exploring the latent potential of different S. cerevisiae strains, the authors show that the allele pool of various strains is a valuable engineering resource to enhance secretion in yeast. Abstract : High levels of recombinant cellobiohydrolase I secretion in Saccharomyces cerevisiae still remains a limitation for efficient lignocellulose hydrolysis. The potential of genome shuffling to consolidate beneficial traits for enhancing cellobiohydrolase I secretion up to 3.5‐fold is demonstrated. It is found that this trait does not confer a general high protein secretion phenotype, as the enhancement is only observed for the secretion of cellobiohydrolase I.